Improvement in visual perception after high-frequency transcranial random noise stimulation (hf-tRNS) in those with migraine: An equivalent noise approach. (15th October 2021) - O'Hare, Louise; Goodwin, Peter; Sharp, Alex; Contillo, Adriano; Pavan, Andrea
Abstract: Migraine is a common neurological disorder with strong links to vision. Interictal migraine is thought to be characterised by internal noise in the brain, possibly due to increased variability in neural firing, which can be estimated using equivalent noise tasks. High-frequency transcranial random noise stimulation (hf-tRNS) can be used to modulate levels of internal noise in the brain, and so presents a possible therapy to redress noise levels in the migraine brain. This is a case-control study using a 2-alternative forced choice (2AFC) design. Hf-tRNS and Sham control stimulation were used alongside a global motion direction discrimination task and visually based equivalent noise tasks. The migraine group demonstrated increased baseline internal noise levels compared to the control group. Internal noise levels, and sampling, were reduced using hf-tRNS but not Sham stimulation. However, there were no differences in terms of coherence thresholds, slopes, and lapse rate for global motion discrimination between the two groups. This is the first demonstration of the possibility of decreasing internal noise levels in migraine using hf-tRNS. Future work could explore the possibility of neurostimulation as a therapy for migraine. Highlights: Equivalent noise task allows estimation of internal noise in the visual system. Internal noise levels increased in migraine on motion-based perception task. Internal noise can be reduced by hf-tRNS. Possible application of hf-tRNS after research into stimulation protocols.